Development of membrane anaerobic system (MAS) for palm oil mill effluent (POME) treatment - Nor Shafiqah, Mohd Nasir (2013)
Palm oil is one of the world most rapidly expanding industries. Oil palm industry currently occupies the largest acreage farm land in Malaysia. This industry contributes towards economic growth and rapid development but unfortunately as well as environmental issues. One of the wastes generated from the palm oil industry known as palm oil mill effluent (POME) can contributes to the environmental issues if it is not treated properly before discharging to the environment. In this study, POME treatment was carried out in a laboratory scale membrane anaerobic system (MAS) that shows highly potential to overcome the environmental problems. The MAS consists of cross flow ultrafiltartion membrane for solid-liquid separation with operating pressurel .5 to 2.0 bars. The fed consists of 30 L of POME used inside the reactor and the hydraulic retention time (HRT) ranged between 1 to 4 days to allow the acclimization phase of the wastewater. Based on the results obtained, the percentage of methane production ranged from 60.00% to 69.79% per day. The overall percentage removal efficiency for the parameters measured in this experiment includes the percentage of BOD removal range from 61.45% to 72.66%, percentage of TSS removal range from 86.05% to 88.94%. There are also measurement for the percentage removal of ammonia with removal efficiency of 20% to 28.94% and the percentage removal of nitrate presence in the POME with removal percentage of 45% to 77.89% efficiency. The MAS performance was affected by the solid retention time, hydraulic retention time, organic loading rates, pH and operating temperature. Hence, NMS is the suitable alternatives for treating the wastewater. The production of methane gas from this process also can be considered as the valuable product and as one type of energy source.